Truly, madly, deeply : a novel - Bellefleur, Alexandria (Avon, an imprint of HarperCollinsPublishers, 2024)
Signing on to record a podcast sharing relationship advice, best-selling romance novelist Truly Livingston finds herself bickering with a cynical divorce lawyer and walks out, but when he tracks her down, asking for a fresh start, they go from enemies to something else entirely.